2005
DOI: 10.1136/bjsm.2003.011478
|View full text |Cite
|
Sign up to set email alerts
|

Differences in sole arch indices in various sports

Abstract: Background: There are controversial data about the relation between foot morphology and athletic injuries of the lower extremity. Studies in soldiers have shown some relationship, whereas those involving athletes have not shown any significant relationship. The reason for these differences is not clear. Objective: To determine the effect of various sports on sole arch indices (AIs). Method: A total of 116 elite male athletes (24 soccer players, 23 wrestlers, 19 weightlifters, 30 handball players, and 20 gymnas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…Recently reported study demonstrated that arch indices were signiˆcantly diŠerent followed by each sport players, including soccer players, wrestlers, weightlifters, handball players, and gymnasts. Especially, wrestlers and gymnasts shown a reduction of foot arch through increasing of diagonal force on metatarsal head (Aydog et al, 2005). In addition, previous research reported that gymnasts shown an attenuation of foot arch following training period in from teenage to 20¿30 ages (Staheli et al, 1987).…”
Section: Discussionmentioning
confidence: 94%
“…Recently reported study demonstrated that arch indices were signiˆcantly diŠerent followed by each sport players, including soccer players, wrestlers, weightlifters, handball players, and gymnasts. Especially, wrestlers and gymnasts shown a reduction of foot arch through increasing of diagonal force on metatarsal head (Aydog et al, 2005). In addition, previous research reported that gymnasts shown an attenuation of foot arch following training period in from teenage to 20¿30 ages (Staheli et al, 1987).…”
Section: Discussionmentioning
confidence: 94%
“…The arch of the foot should provide for an elastic, springy connection between the regions of the foot. 6,8,9,22,43,50 This relationship allows for normalized weight bearing and the dissipation of ground reaction forces before they are transmitted to the leg and thigh. 6,8,9,22,43,50 It is also known that foot arch posture changes over time because of factors such as growth, aging, and disease-dependent degenerative processes during life.…”
Section: Distribution Of Foot Arch Posture and Surgerymentioning
confidence: 99%
“…6,8,9,22,43,50 This relationship allows for normalized weight bearing and the dissipation of ground reaction forces before they are transmitted to the leg and thigh. 6,8,9,22,43,50 It is also known that foot arch posture changes over time because of factors such as growth, aging, and disease-dependent degenerative processes during life. 8,9,43,50 Redmond et al 50 discovered that a Ushaped relationship existed for age, with minors and older adults exhibiting higher foot posture index scores than the general adult population.…”
Section: Distribution Of Foot Arch Posture and Surgerymentioning
confidence: 99%
See 2 more Smart Citations